Comparison of four nutritional screening tools in perioperative elderly patients: Taking orthopedic and neurosurgical patients as examples - Gong, Jie; Zuo, Silu; Zhang, Jie; Li, Li; Yin, Jie; Li, XinYi; Yu, Fengmei; Hu, Wen (Frontiers in Nutrition, 2023)
Background and aims Malnutrition is widely present in elderly surgical patients and is highly correlated with prognosis after surgery. However, studies comparing the effectiveness of comprehensive nutritional screening tools in geriatric surgical patients have not yet been published. The nutritional risk among elderly orthopedic and neurosurgical patients and their associated clinical indicators and outcomes was assessed using four screening tools. The aim of this study was to explore suitable tools for screening the nutritional status and identify their potential to act as prognostic indicators. Methods The Nutritional Risk Score 2002 (NRS2002), Mini Nutritional Assessment - Short Form (MNA-SF), Geriatric Nutritional Risk Index (GNRI), and Prognostic Nutritional Index (PNI) were all performed within two days of admission and before surgery. The relationships between nutritional risk classifications and conventional nutritional markers, complications and length of hospital stay (LOS) were evaluated. Results In this study, a total of 167 orthopedic patients and 103 neurosurgical patients were evaluated. In neurosurgical patients, the rates of malnutrition or patients at risk of malnutrition according to the MNA-SF, GNRI, NRS2002 and PNI were 26.4, 24.6, 8.4, and 12.6%, respectively. According to the NRS2002 and PNI, the rates of old neurosurgical patients who were malnourished or at risk of malnutrition were 14.6 and 3.9%, respectively, which were lower than the results assessed by the MNA-SF (24.3%) and GNRI (15.5%). Multiple regression analysis revealed a significant relationship between the PNI (malnourished vs.well-nourished, OR = 5.39, 95% CI:1.11-26.18, P = 0.037), GNRI (at risk vs.no risk, OR = 3.96, 95% CI: 1.01-15.45, P = 0.048) and the complications in orthopedic patients. Only GNRI was significantly related to LOS > 7 days (at risk vs.no risk, OR = 4.01, 95% CI: 1.64-9.80, P = 0.002). For neurosurgical patients, an association between GNRI and LOS > 8 days was discovered (at risk vs.no risk, OR = 3.35, 95% CI: 1.03-10.86, P = 0.002). Conclusion Among the four nutritional risk screening tools, the GNRI exhibited better predictive value for short-term outcomes in elderly perioperative orthopedic and neurosurgical patients, thereby suggesting that it might be a more suitable tool for nutritional risk screening. Additional studies are required to determine the applicability of GNRI in other surgical fields.